Acute hematogenous osteomyelitis in children: a case series - Komang Agung Irianto; Adhinanda Gema; William Putera Sukmajaya (Paediatrica Indonesiana, 2019)
Background Chronic osteomyelitis is still a major cause of morbidity and disability in children living in developing countries. Neglect of acute osteomyelitis and its progression to chronic osteomyelitis leads to significant morbidity. This report is the first series to describe such cases in Indonesia. Objective To describe 12 pediatric cases of chronic osteomyelitis in order to remind clinicians about the debilitating complications of musculoskeletal infection. Methods This report is a case series of 12 children with chronic osteomyelitis admitted to dr. Soetomo General Hospital, Surabaya, East Java, in 2011-2017. We acquired data from medical records. The patients' quality of life was measured using the Child Health Assessment Questionnaire Disability Index (C-HAQ-DI). Results The patients' mean age was eight years and they were predominantly male. The most common infection location was the femur (7/12). Microbial cultures were positive in 9/12 of cases, predominantly with Staphylococcus aureus. Erythrocyte sedimentation rate (ESR) was elevated in 11 patients. All patients were diagnosed late, with an average delay of presentation to Orthopedics of 10.5 months. Most of patients experienced mild to moderate disability after the disease, as assessed by the C-HAQ-DI. Conclusion Diagnosis of osteomyelitis in children is quite difficult, given the lack of specific diagnostic tests. Delayed diagnosis and inappropriate treatment may result in long-term morbidity and disability. Clinicians should have an increased awareness of the clinical features of osteomyelitis, including unusual presentations such as calcaneal osteomyelitis.